Diet of the Tristan rock lobster Jasus tristani following the 2011 soya spill at Nightingale Island - Jones, Luke (Marine Research (MA-RE) Institute, 2017)
The spiny lobster Jasus tristani inhabits the Tristan da Cunha Island archipelago in the South Atlantic Ocean 2,400km from the West coast of South Africa. It is commercially exploited across the archipelago and is the main economic source of income for the local government as it accounts for nearly 80% of the local gross domestic product. The commercial rock lobster industry was established in 1949, and the fishery is currently recognised as sustainable, and as a result was awarded a Marine Stewardship Council Certification in 2011. That same year however, the sinking of the OLIVA at Nightingale Island spilt 60,000 tonnes of soya beans (Glycine max), greatly affecting the local benthic environment, and with probable consequences for the local food web, including the diet of J. tristani. It is still unclear whether the soya beans are still on the seafloor at Nightingale Island as there have been no scientific surveys conducted since the spill. Using samples from 2015, I assessed whether the diet of the lobsters from Nightingale Island differs from that of lobsters from the unaffected Tristan and Inaccessible Islands, and whether there is any evidence of soya in the diet of the lobsters from Nightingale Island. In addition, I examined whether diet differed between lobsters of small or large size, and between shallow and deep depths. In total, 540 lobsters were sampled across the three islands, and a combination of gut content and stable isotope (SI) analysis was conducted to assess the dietary components of the lobsters. Gut fullness was significantly less at Nightingale Island suggesting there may be less food available on the reef. Statistical analyses showed that diet differed between all islands, depths and sizes, although this was difficult to ascertain from visual multidimensional scaling plots as diet showed considerable overlap and variability both within and between islands, depths and sizes. The stable isotope analysis showed significant differences in nitrogen levels among the three